Epigenetic Regulation of Kupffer Cell Function in Health and Disease - Bennett, Hunter; Troutman, Ty D.; Sakai, Mashito; Glass, Christopher K. (Frontiers in Immunology, 2021)
Kupffer cells, the resident macrophages of the liver, comprise the largest pool of tissue macrophages in the body. Within the liver sinusoids Kupffer cells perform functions common across many tissue macrophages including response to tissue damage and antigen presentation. They also engage in specialized activities including iron scavenging and the uptake of opsonized particles from the portal blood. Here, we review recent studies of the epigenetic pathways that establish Kupffer cell identity and function. We describe a model by which liver-environment specific signals induce lineage determining transcription factors necessary for differentiation of Kupffer cells from bone-marrow derived monocytes. We conclude by discussing how these LDTFs drive Kupffer cell behavior during both homeostasis and disease, with particular focus on the relevance of Kupffer cell LDTF pathways in the setting of non-alcoholic fatty liver disease and non-alcoholic steatohepatitis.